Enhancing the design of wine labels - Crichton-Fock, Anders; Spence, Charles; Mora, Maria; Pettersson, Nicklas (Frontiers in Psychology, 2023)
The knowledge accrued through research in the domain of crossmodal correspondences has had a significant influence on a diverse array of disciplines, including behavioral studies, neuroscience, computational modeling, and notably, marketing, with the objective of aligning sensory experiences to help shape patterns of consumer behaviour. A study is reported that a necessary prerequisite, enabling these consumers to make informed choices that align with their preferences, even in the absence of previous sensory encounters. Nonetheless, semiotic investigations underscore the significance attributed to symbolic components such as signs, logos, colors, gestures, and linguistic cues. Research emanating in the field performing multisensory studies, presents a counterpoint to prevailing communication paradigms, advocating for a heightened incorporation of metaphors, analogies, symbols, metonymies, and allegories. This alternative approach aims to enhance the efficacy of communication strategies, offering a more profound and evocative means of conveying intricate messages on a more holistic level.A questionnaire was sent to a specific group of engaged wine consumers (n=329). Besides questions regarding demographics, purchase behavior, and consumption behavior, the questionnaire included examples of multisensory communication through a selection of symbols, as well as alternative wine information.Results: The results showed significant correlations between demographics, consumption behavior, and attitudes towards the tested multisensory symbols and alternative information, thus helping to gain a better understanding of the sensory properties that should be communicated on wine labels. Discussion: The findings reported here highlight the effectiveness of visual crossmodal communication arises as a promising pathway capable of skillfully capturing consumer attributes, conveying multisensory experiences, and portraying the comprehensive timeline of taste evolution. As a result, it assumes a pivotal role as a communicative tool for intricate consumables, like wine, functioning at the crossroads of visual and sensory dimensions.